RENAL DENERVATION IN RESISTANT ARTERIAL HYPERTENSION - V. A. Sulimov; A. V. Rodionov; A. A. Svetankova; I. E. Deneka (Рациональная фармакотерапия в кардиологии, 2015)
A new method of non-drug treatment of resistant hypertension – renal denervation is considered. General information about resistant hypertension, method of renal denervation, the results of clinical studies on efficacy and safety, as well as own clinical case are presented.